Kompetensi Pamong Belajar Program Kesetaraan Paket C Terhadap Peningkatan Hasil Belajar Warga Belajar Di SKB Situbondo - Wahyuda, Dika; Imsiyah, Niswatul; Alkornia, Sylva (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
The learning process in non-formal education will be carried out well if it is supported by competent tutors because its role and ability in creating an effective learning environment will have a major effect on improving student learning outcomes. The purpose of this study was to determine the competence of the tutor for the package C equivalence program in improving the learning outcomes of students at SKB Situbondo. The method used in this study uses a qualitative approach with a descriptive type of research. The results showed that the tutor in improving the learning outcomes of the citizens in SKB was measured by the ability of the tutor himself. A tutor has adequate knowledge standards so that he can manage learning which includes student understanding, learning design and implementation, evaluation of learning outcomes and development of students to actualize their various potentials.